2015
DOI: 10.1177/1099800415577801
|View full text |Cite
|
Sign up to set email alerts
|

Association of Job Strain With Cortisol and Alpha-Amylase Among Shift-Working Health Care Professionals in Laboratory and Field

Abstract: Although the prevalence of work-related stress has increased, knowledge on the contributions of that stress to long-term adverse health effects is still lacking. Stress biomarkers can reveal early signs of negative health effects, but no previous studies have measured both acute stress reactions and long-term exposure to job strain using both salivary cortisol and α-amylase (AA). The present study examines the association between job strain and these biomarkers among shift-working female health care profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
(82 reference statements)
0
11
0
1
Order By: Relevance
“…A further study found cardiovascular reactivity was positively associated with job strain in a group of workers with a mean age 51.9 years, and was higher among those over 50 (Clays et al, 2007). Equally, work-related stress has also been associated with higher cortisol reactivity (Hausser et al 2011;Karhula et al 2016;Steptoe et al 2000). However, current evidence suggests that the relationship between work and stress reactivity is complex (Rudolph et al 2016) and the majority of studies have not measured or found consistent results for both cardiovascular and cortisol responses to acute stress, or have not measured resilience.…”
Section: Introductionmentioning
confidence: 90%
“…A further study found cardiovascular reactivity was positively associated with job strain in a group of workers with a mean age 51.9 years, and was higher among those over 50 (Clays et al, 2007). Equally, work-related stress has also been associated with higher cortisol reactivity (Hausser et al 2011;Karhula et al 2016;Steptoe et al 2000). However, current evidence suggests that the relationship between work and stress reactivity is complex (Rudolph et al 2016) and the majority of studies have not measured or found consistent results for both cardiovascular and cortisol responses to acute stress, or have not measured resilience.…”
Section: Introductionmentioning
confidence: 90%
“…The LJS group participants were physically active more often than the HJS group participants (p < .02). The descriptive statistics are shown in Table 1, and have been previously published by Karhula et al [24,29] Statistical analysis A logarithmic transformation of the stress biomarker original values was used due to skewed distributions. The area under the curve with respect to ground (AUCg, nmol/l × min) and the area under the curve with respect to increase (AUCi, nmol/l × min) [31] were calculated for logarithmic transformed stress biomarkers assuming linearity between the consecutive measurement points (Figure 1).…”
Section: Participantsmentioning
confidence: 99%
“…The mean saliva sample collection times were during the morning shift measurements on average at 05:27 (AW), 05:57 (AW30), and 22:36 in the evening, during the night shift measurements at 08:08 (AW), 08:41 (AW30), and 08:06 the next morning before going to sleep, and during the day of measurements at 07:56 (AW), 08:21 (AW30), and 21:34 in the evening. The AW and AW30 samples were collected on average 6 and 35 min after sleep end (determined from actigraph data) in the morning shift, 8 and 38 min after sleep end in the night shift, and 6and 35 min after sleep end on the day off [29].…”
mentioning
confidence: 99%
“…Stress biomarkers aid in detecting early signs of developing negative health outcomes. [25] Cortisol hormone is a biomarker released in response to stress that is considered to be an objective measurement. [26] Under stress, activation of the HPA axis releases hormones that signal the adrenal cortex to produce cortisol.…”
Section: Literature Reviewmentioning
confidence: 99%